Communicating the word : revelation, translation, and interpretation in Christianity and Islam : a record of the seventh Building Bridges seminar convened by the Archbishop of Canterbury Rome, May 2008 - Marshall, David, 1963- (UPCC book collections on Project MUSE., 2011)
"Communicating the Word is a record of the 2008 Building Bridges seminar, an annual dialogue between leading Christian and Muslim scholars convened by the Archbishop of Canterbury."--Back cover.